An Interdisciplinary Approach: Identity Design of "Indonesian Cultural" Art Studio - Sri Wahyuning Septarina; Jessica Irena Ridwan (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2021)
Identity is a personality that shapes distinguishing traits of the subjects. Multicultural Indonesians have their own cultural value as their identity. Indonesian cultural diversity has been rooted deep down and has become a foundation in the life of its society. Indonesian cultural art is classified into 5 categories, which are dance, music, theatre, visual art, and literature. The purposes of this research are: 1. Develops the value of Indonesian cultural identity, 2. Provides the space of intertwined culture and identity through interdisciplinary approach, 3. Integrating Indonesia cultural arts as a national identity which would unite our country. Descriptive quantitative method is used to elaborate the fundamental elements of visual identity design with the literature-based data collecting techniques. Data will be processed with visual communication theories and interdisciplinary approach in order to attain the concept of Indonesian cultural studio identity designs. The designs are adopted from artistic daily activities which have contributed to preserving Indonesian culture, collaborated with nationalism characteristics.